Pengaruh Pelapisan Menggunakan Antioksidan Alami Dari Kulit Buah Naga Pada Periode Simpan Berbeda Terhadap Viabilitas Benih Timun Apel (Cucumis sp.) - Fatha, Muhammad Rafi Aryu; Azizah, Elia; Samaullah, H.M. Yamin; Syafi’i, Muhammad; Saputro, Nurcahyo Widyodaru (JURNAL AGROPLASMA, 2024)
The deterioration of seed quality cannot be repaired or prevented, but it can be minimised by proper processing and storage. An alternative to overcome this problem is to provide seed coating treatment. The study aimed to determine the effect of antioxidant coating of red dragon fruit peel on the viability of apple cucumber seeds (Cucumis. Sp) and to obtain the best dose of dragon fruit peel antioxidant to coat apple cucumber seeds (Cucumis sp). The experiment was conducted at Lab.Agronomy, Faculty of Agriculture, Singaperbangsa University of Karawang, starting from Nov. 2023 - Mar. 2024. The experimental method used was experimental method and the experimental design used was a completely randomised design (CRD) consisting of 15 treatments in 3 replications, so there were 45 experimental units. The effect of treatment was analysed with variance analysis and if the F test at the 5% level was significant, then to find out the best treatment continued with the DMRT (Duncan Multiple Range Test) further test at the real level of 5%. The results showed a significant effect of treatment on germination, vigour index, and growth speed. The best treatment was obtained in treatment B (0 g + 8 weeks) which was able to produce the highest value in the parameters of germination power of 75.76%, vigour index of 9.09%, and growth speed of 10.30%/day. Keywords: apple cucumber, seed coating, antioxidant, dragon fruit peel, seed storage